Performance analysis of ad-hoc routing protocols in smart metering infrastructure - Farooq, H. (2013)
Smart Metering Infrastructure is an integral part of the Smart Power Grid Revolution. Wireless Ad-hoc Network is considered a promising candidate for enabling smart metering communications. This paper investigates which kind of Ad-hoc routing scheme (proactive, reactive and hybrid) will be most suitable for Smart Metering Infrastructure. Simulation studies utilizing three different topologies are conducted to analyze the performance of the protocols and relative comparison is provided based on four metrics of (i) Packet Delivery Ratio, (ii) Average Energy Consumption of Nodes (iii) Average End-End Delay and (iv) Normalized Routing Load. Â© 2013 The Science and Information Organization.